Políticas de avaliação docente no ensino superior: o significado da gratificação de estímulo à docência (GED) na Universidade Federal de Uberlândia - Rocha, Vânia Amaral da (2005)
The present research has its axle- tree in the field of evaluation of politics for the superior education, established since the nineties from the XX century. More specifícally, it pursuits to learn the meaning of the implement of Teaching Incentive Gratification (TIG) at the Federal University of Uberlândia (UFU). For so, it has been analyzed the new configurations in the organization of the production, of the work and of the State in the context of the current Brazilian educational reformation in times of economical globalization and the advance of neoliberal ideal. It has been evidenced a whole of structural standard adopted by the Brazilian State under orientation of the multisided organisms of financing, in particular, the World Bank, in order to find a budget equilibrium via reduction of public expenses. In the specific field of superior education, the adopted modifications since Fernando Henrique Cardoso -FIIC governs (1995 - 2002) have returned to the expansion of the private superior education by the side of the weakness of the public section. Such configuration, founded in the institutional differentiation and Services diversification principies, represented the constitution of a new organizational pattern for Federal Institutions of Superior Education (FISE) based on the market logic which associates flexibilization, competitivity and evaluation in order to obtain higher productive index. The emphasis in the evaluation corresponded to the great strategy of the federal govern of commercialization of the superior education, according to the academic efficiency and efficacy criterion. Methodologically, after an analysis of the social -historical conditioning which permeated the superior education development in Brazil, at the end of the XX century and using the technique of the content analysis of documents produced in the period of 1998 - 2003 at UFU, we focalize the study around the process of TIG implement at UFU. It has been evident that, in one hand, this process has developed without the necessity of a deep debate by the academic community and systemized about its meaning and dimension. In the other hand, it has also been evidenced, the homogenized and disaggregated character of TIG, besides its strong productive perspective, because the TIG objected to valorize, initially, the academic titulation and finish with the isonomic readjusts of salary by means of gratilication based on performance. In a little time, the TIG could reach one of its basic finalities: stimulate changes in the teachers' behaviour and in the nature of academic work, according to the politics and with the logic of the superior education. It has also been responsible, for one institutional worry to adequate, to register, to control and to uniformize teachers' performance, in the areas of teaching, research, extension and administration. Besides, each teacher has passed to pawn in adequate their academic activities to the rnost punctuated items of TIG. The “class”, especially in the graduation, has become the rnost significative object of this adjustment. Sticking out, yet, as the implementation of this gratification in the process of flexible standardization of academic work, in the FISE, in the proportion that it propitiates a salary differentiation, it stimulates the competivity among teachers and, in this way, denies the public university model which associates the education, the research and extension as a guide principie to the education quality.